Adaptation and psychometric properties of the Disgust Scale-Revised in a Peruvian sample - Mauricio Enrique Silva-Alegria (International Journal of Personality Psychology)
Objective: Adapt and validate the psychometric properties of the Disgust Scale-Revised in Peruvian Adults. Method: A non-probabilistic, snowball sample of 335 Peruvian adults was taken. For content validity, the clarity of the items was evaluated using Aiken's V. For internal structure validity, the fit indices of a series of CFAs were evaluated for the one, two, and three-factor models. For external validity, the DS-R constructs were correlated with the purity subconstruct of the Moral Foundations Questionnaire. For reliability, the ordinal alpha and the omega coefficient were used. Results: Acceptable fit indices were obtained for the two and three-factor models. Acceptable reliability indices for the core disgust and animal reminder scales were obtained. And small, significant positive correlations were obtained between the contamination and animal reminder factors with the purity scale of the MFQ. In conclusion, the DS-R is an instrument with acceptable psychometric properties for research contexts, although some adjustments could be made to increase the reliability of the contamination scale.